(untitled) (Bangladesh Pharmaceutical Journal, 2019)
The present study was aimed for the evaluation of analgesic, anti-diarrheal and anti-depressant activities of methanol crude extract of Bridelia verrucosa leaves in Swiss albino mice. The analgesic activity was assessed by formalin-induced paw licking method, where the crude extract of B. verrucosa (400 mg/kg, b.w.) exhibited 54.55% reduction of licking response in mice as compared to 69.09% reduction exhibited by standard acetylsalicylic acid. In the castor oil-induced diarrhea in mice, the plant extract at the dose of 400 mg/kg, b.w., demonstrated 57.67% reduction of diarrheal feces in mice. The antidepressant activity of the plant extract was evaluated through phenobarbitone-Na induced sleeping time test. The methanol extract of B. verrucosa and its different Kupchan fractions were also subjected to screenings for membrane stabilizing and cytotoxic activities using acetylsalicylic acid and vincristine sulphate as standard, respectively. Bangladesh Pharmaceutical Journal 22(1): 50-55, 2019